Binary Equilibrium Adsorption Data and Comparison of Zeolites with Activated Carbon for Selective Adsorption of CO from CH - Javad Tamnanloo; Shohreh Fatemi; Ayub Golmakani (Adsorption Science & Technology)
A commercial-type activated carbon (AC) and three zeolitic materials, namely, zeolite socony mobil-5 (ZSM-5), Silicalite-1 and SAPO-34, were comparatively studied for single and binary equilibrium adsorptions of CO 2 and CH 4 . The adsorption isotherm data were obtained experimentally by volumetric method at room temperature (30 °C) in the pressure range of 0–10 bar. The isotherms were used to determine the selectivity of the absorbents for CO 2 /CH 4 . The single isotherm data showed AC had the highest adsorption capacity for both CO 2 and CH 4 ; however, the CO 2 /CH 4 ideal selectivity of AC was less than that of the zeolitic materials. These results suggest that AC is a suitable material for adsorption of both CO 2 and CH 4 from flue gas, whereas it would not be suitable for selective separation of CO 2 from CH 4 . The zeolitic materials, namely, ZSM-5, Silicalite-1 and SAPO-34, had good adsorption capacity for CO 2 against CH 4 . The molecular sieving property of SAPO-34 showed higher CO 2 selectivity than that of ZSM-5 and Silicalite-1. Further investigations were conducted on SAPO-34 for binary mixtures of CO 2 –CH 4 with different compositions at various total pressures. The results showed that strong adsorption of CO 2 caused significant decrease in CH 4 adsorption, and therefore, the real selectivity of CO 2 /CH 4 was improved more than the ideal selectivity. Real selectivity of CO 2 /CH 4 at 2.5 bar pressure for an equimolar mixture was 20% more than the ideal selectivity and by increasing total pressure up to 4.5 bar its value improved up to 70% more than the ideal selectivity.